# Evaluate the indefinite integral integrate of x^3*5^(-x^2)dx You should use the following substitution such that:

x^2 = t => 2xdx = dt => xdx = (dt)/2

int x^2*5^(-x^2)*xdx = int t*5^(-t) (dt)/2

You need to use integration by parts such that:

int udv = uv - int vdu

u = t => du = dt

dv =...

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

You should use the following substitution such that:

x^2 = t => 2xdx = dt => xdx = (dt)/2

int x^2*5^(-x^2)*xdx = int t*5^(-t) (dt)/2

You need to use integration by parts such that:

int udv = uv - int vdu

u = t => du = dt

dv = 5^(-t) dt => v = -5^(-t)/(ln 5)

int t*5^(-t) dt = -t*5^(-t)/(ln 5)+ int 5^(-t)/(ln 5)

int t*5^(-t) dt = -t*5^(-t)/(ln 5) - 5^(-t)/(ln^2 5) + c

Substituting back x^2  for t yields:

int x^2*5^(-x^2)*xdx = (1/2)(-x^2*5^(-x^2)/(ln 5) - 5^(-x^2)/(ln^2 5)) + c

Hence, evaluating the given integral yields int x^3*5^(-x^2)dx = (1/2)(-x^2*5^(-x^2)/(ln 5) - 5^(-x^2)/(ln^2 5)) + c.`

Approved by eNotes Editorial Team